1997
DOI: 10.1073/pnas.94.15.8121
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Gαq overexpression induces cardiac contractile failure in mice

Abstract: The critical cell signals that trigger cardiac hypertrophy and regulate the transition to heart failure are not known. To determine the role of G␣q-mediated signaling pathways in these events, transgenic mice were constructed that overexpressed wild-type G␣q in the heart using the ␣-myosin heavy chain promoter. Two-fold overexpression of G␣q showed no detectable effects, whereas 4-fold overexpression resulted in increased heart weight and myocyte size along with marked increases in atrial naturietic factor (Ϸ5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
454
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 577 publications
(485 citation statements)
references
References 47 publications
30
454
0
1
Order By: Relevance
“…On the other hand, hearts in the Kidney KOs appeared virtually normal, indicating that vascular injury and fibrosis in the heart were also consequences of elevated blood pressure rather than local actions of cardiac AT 1 receptors. Cardiac hypertrophy is associated with characteristic alterations in gene expression, including up-regulation of ANP and BNP (31,32), and recapitulation of fetal patterns for expression of myosin heavy chains (33,34). It has been suggested that activation of AT 1 receptors in cardiomyocytes may be sufficient to trigger this transcription profile (34,35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, hearts in the Kidney KOs appeared virtually normal, indicating that vascular injury and fibrosis in the heart were also consequences of elevated blood pressure rather than local actions of cardiac AT 1 receptors. Cardiac hypertrophy is associated with characteristic alterations in gene expression, including up-regulation of ANP and BNP (31,32), and recapitulation of fetal patterns for expression of myosin heavy chains (33,34). It has been suggested that activation of AT 1 receptors in cardiomyocytes may be sufficient to trigger this transcription profile (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac hypertrophy is associated with characteristic alterations in gene expression, including up-regulation of ANP and BNP (31,32), and recapitulation of fetal patterns for expression of myosin heavy chains (33,34). It has been suggested that activation of AT 1 receptors in cardiomyocytes may be sufficient to trigger this transcription profile (34,35). However, as we observed with cardiac hypertrophy and pathology, activation of AT 1 receptors in the heart is not responsible for characteristic gene expression patterns associated with Ang II infusion; these are also triggered by elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Vivo and ex Vivo Left Ventricular Function-Left ventricular contractile parameters were determined in closed-chest anesthetized mice using a 1.4-French scale Millar MIKRO-TIP catheter, as previously described (25). Contractile parameters of isolated hearts were also determined in Langendorff mode at 37°C with a constant perfusion pressure of 50 mm Hg, as described previously (23).…”
Section: Methodsmentioning
confidence: 99%
“…These paradigms were recapitulated in transgenic mice generated in Dorn's laboratory. Initial studies with these transgenic mice showed that a modest (four-fold) overexpression of Gaq in the myocardium lead to development of a stable form of cardiac hypertrophy (D'Angelo et al, 1997). However, when these mice were subjected to the neurohumoral or hemodynamic stresses associated with parturition (Adams et al, 1998b) or to chronic pressure overload Adams et al, manuscript in preparation) cardiac failure rapidly developed in association with increased cardiomyocyte apoptosis.…”
Section: Gaq Signaling In Apoptosis and Failurementioning
confidence: 99%